Moralitas Pemuda Dalam Realitas Keluarga Era Milenial: Upaya Kontrol Sosial Terhadap Dekadensi Moral Pemuda - Kemas Ridho Aufa; Helmi Muti Sofie (Prodi Sosiologi FISIP Universitas Teuku Umar, 2022)
This research aims to find out how the influence of the Industrial Revolution 4.0 on the lives of millennials and their social functions in the reality of social life. This research is a sociological juridical research with a qualitative method approach which aims to reveal qualitative information, through a correct, systematic and accurate description of the problem. The results show that the millennial generation has advantages in the realm of technology and industry in terms of social functions. However, not many millennials are able to adapt to technological developments, so that the crisis of trust in life and depression become psychosocial problems that cause moral decline for this generation. In this case, Travis Hirschi suggests that there are four points as an effort to improve moral decline, namely Attachment, Comitment, Involment, and Belief.